A New Theoretical Framework for Therapeutic Landscapes: Coastal (Blue), Forest (Green), Spiritual "Power Spots" (Gold) and Wildernerss (Dark/White) - Azevedo, António (Journal of Tourism, Sustainability and Well-being, 2020)
This paper aims to discuss the healing and wellbeing effects induced by places and landscapes such as coastal (blue) areas and green spaces. Adopting a holistic approach, the paper fills a gap by exploring the therapeutic benefits of other short-term experiences such as: spiritual/ introspective (gold), sensation seeking/excitement, achievement-oriented, symbolic and transformative experiences. “Dark” and “white” sceneries such as risk recreation and pilgrimage to “land’s ends”, dystopian places and (white) extreme wilderness were also analyzed. The negative externalities caused by neighborhood social and physical disorder (grey zones) complete the “pallet of colors”. This conceptual paper fills a gap providing a new tool to map place brands according to two positioning axis: 1) Physical Health (passive absorption/ residential exposure) (positive versus negative impact); 2) Spiritual versus Excitement/Self-achievement (active way/ short exposure). Furthermore, it proposes also a new theoretical framework for the “salutogenic health system” and for the “governance support system”. The paper’s contributions will help place brand managers, public decision makers and tourism operators to develop innovative place based policies using those health benefits as a driver for place branding positioning.